2010
DOI: 10.1186/1477-7819-8-16
|View full text |Cite
|
Sign up to set email alerts
|

A case of high-grade leiomyosarcoma of the bladder with delayed onset and very poor prognosis

Abstract: Mesenchymal tumors represent a small number of bladder cancer cases. Leiomyosarcoma is the most common histology with over 100 cases reported in the whole literature. This tumor is been historically considered as highly aggressive and showing a poor prognosis. Despite very low survival rates showed in older reports, some authors indicate that some patients could have a better outcome. We report a review of the literature and a case of high-grade LMS of the bladder in a 68 years old woman. Diagnosis was delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 17 publications
0
22
0
4
Order By: Relevance
“…There was no hematuria. The presentation in our case was at a relatively earlier age than in other cases [3-5]. Surgery with a tumor-free margin is the basic surgical principle for the treatment of leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…There was no hematuria. The presentation in our case was at a relatively earlier age than in other cases [3-5]. Surgery with a tumor-free margin is the basic surgical principle for the treatment of leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 67%
“…Tumors of a high grade and advanced stage should be treated with radical cystectomy and urinary diversion. Partial cystectomy is reserved for tumors that present at an early stage and a low grade [4,5]. The best prognostic factor is the presence of tumor-free margins.…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature revealed that the overall prognosis is variable but generally poor . In a recent series by Lee et al , seven sarcomas of bladder were studied, and the estimated 5‐year survival rate was 73%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no consensus regarding the standard treatment protocol. The leiomyosarcomas of the bladder are usually aggressive tumors with very poor prognosis usually managed with radical cystectomy . We report a case of a 54‐year‐old woman with locally advanced leiomyosarcoma of the bladder who was successfully treated with partial cystectomy and wide local excision.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus about the standard treatment, and because of the very low incidence, little is known about the natural history and prognosis of the tumour. Leiomyosarcomas have a poor prognosis, especially if they are of high-grade and stage [1] . Herein we review previous cases and report two new cases of bladder leiomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%